Exercise-Loaded Indocyanine Green Fluorescence Lymphangiography for Diagnosing Lymphedema - Matsumoto, Kumiko; Shinaoka, Akira; Yamada, Kiyoshi; Kimata, Yoshihiro (Journal of Reconstructive Microsurgery, 2019)
Background Indocyanine green (ICG) fluorescence lymphography (ICGLG) that can visualize the lymphatic vessel and its flow noninvasively and dynamically was developed in 2007. It is frequently used to observe the function and pathway of the lymphatic vessels. ICGLG is simple and easy to perform, and it is useful for understanding the condition of the lymphatic system in real time. However, its protocol is not standardized. In addition, the lymphatic flow is enhanced by an exercise load such as walking. Till now, there is no report of exercise-loaded ICGLG. Therefore, we aimed to shorten the examination time and establish a standard ICGLG protocol.Methods We examined 63 patients (126 lower limbs) who visited our clinic for lower extremity edema. We observed detailed images of exercise-loaded ICGLG and examined the changes in findings over time in affected legs classified according to the International Society of Lymphedema. After ICG was injected, the participants exercised for 30 minutes. We observed the farthest proximal point where any ICG could be observed and the appearance of dermal backflow (DB), which is a specific finding of lymphedema, every 5 minutes.Results The proximal migration speed of ICG tended to slow as the disease stage worsened. For all disease stages, after 20 minutes of exercise, the DB appearance rate did not change further. The rates were 0% for legs with stage 0 lymphedema, 50% for legs with stage 1 lymphedema, and 100% for legs with stages 2a and 2b lymphedema.Conclusion The appropriate exercise duration after ICG injection is 20 minutes. ICGLG is useful for screening for lymphedema.
Keywords: indocyanine green fluorescence lymphography; lymphedema; exercise-loaded